THE ROLE OF ETHICAL LEADERSHIP IN ENHANCING EMPLOYEE RETENTION IN MULTINATIONAL CORPORATIONS - Yeti, Yeti (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This research explores the role of ethical leadership in increasing employee retention in multinational companies (MNCs). In the context of intense global competition, high levels of employee turnover pose a significant challenge for MNCs, which can disrupt organizational stability and increase recruitment costs. Through a systematic review of relevant literature, this research identified five key dimensions of ethical leadership that contribute to employee retention: integrity and transparency, fairness and justice, modeling ethical behavior, employee-focused decision making, and a supportive work environment. Findings suggest that ethical leadership not only increases employee job satisfaction and commitment, but also creates a positive organizational culture that supports long-term loyalty. This research provides practical insights for managers and leaders in MNCs to develop leadership strategies that focus on ethics to reduce turnover and increase organizational competitiveness.